2023
DOI: 10.1177/23259671231184400
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Bone Marrow–Derived Mesenchymal Stem Cells for Chronic Patellar Tendinopathy (With Gap >3 mm) in Patients: 12-Month Follow-up Results of a Phase 1/2 Clinical Trial

Robert Soler,
Gil Rodas,
Joan Rius-Tarruella
et al.

Abstract: Background: In a previous study, the authors found that at 6 months after treatment with a 20 × 106 dose of bone marrow–derived mesenchymal stem cells (BM-MSCs), patients showed improved tendon structure and regeneration of the gap area when compared with treatment using leukocyte-poor platelet-rich plasma (Lp-PRP). The Lp-PRP group (n = 10), which had not seen tendon regeneration at the 6-month follow-up, was subsequently offered treatment with BM-MSCs to see if structural changes would occur. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The results of a 12-month study involving participants with patellar tendinopathy showed that BMSC biologic treatment was uncomplicated and safe. The participants showed significant clinical improvements and the tendons examined by magnetic resonance imaging (MRI) showed a more organised structure [37]. Unfortunately, the disadvantage of BMSCs is an increased incidence of ectopic bone formation in the animal's tendons and reduced strength compared with tendons that were not exposed to injury [38].…”
Section: Bone Marrow-derived Mesenchymal Stem (Bmscs)mentioning
confidence: 99%
“…The results of a 12-month study involving participants with patellar tendinopathy showed that BMSC biologic treatment was uncomplicated and safe. The participants showed significant clinical improvements and the tendons examined by magnetic resonance imaging (MRI) showed a more organised structure [37]. Unfortunately, the disadvantage of BMSCs is an increased incidence of ectopic bone formation in the animal's tendons and reduced strength compared with tendons that were not exposed to injury [38].…”
Section: Bone Marrow-derived Mesenchymal Stem (Bmscs)mentioning
confidence: 99%
“…In total, 360 patients underwent PRP injections for PT. Overall, seven articles originated from Italy [ 2 , 4 , 5 , 12 - 15 ]; two each from the USA [ 11 , 16 ], France [ 17 , 18 ], and the Netherlands [ 19 , 20 ]; and one each from Egypt [ 21 ], Turkey [ 10 ], and Spain [ 22 ], as well as a multicenter study that involved hospitals in Italy, Norway, and the USA [ 23 ]. A summary of the study characteristics of the included articles can be found in Table 1 .…”
Section: Reviewmentioning
confidence: 99%
“…After a mean follow‐up period of 5 years, there was a statistically significant improvement in Tegner score, IKDC score and Knee injury and Osteoarthritis Outcome Score symptoms, activities of daily living and sport. Soler et al [ 32 ], did a prospective comparative study between bone marrow‐derived mesenchymal stem cells (BM‐MSCs) and LP‐PRP in 20 patients with chronic patellar tendinopathy. In the first phase of the study, BM‐MSC injection and PRP injection were given to 10 patients each.…”
Section: Introductionmentioning
confidence: 99%